Analisis Ketidakpastian Pengukuran Dimensi Roda Gigi Lurus dengan Alat Ukur Profile Projector - Ulikaryani Ulikaryani; Hamid Abdillah; Hety Dwi Hastuti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
An analysis of the uncertainty value of measuring spur gear dimensions using a profile projector has been carried out. Dimensions of spur gears measured are pitch diameter, root diameter and outside diameter. The manufacture of 3 samples of spur gears was first made with a shape milling machine based on the initial technical data that had been determined. Then measurements were made with a profile projector measuring instrument for the three measuring dimensions, the best repeated measurement average was found in the root diameter measurement for the PJ01 sample of 32.4053 mm with a standard deviation of 0.0077 mm. The uncertainty method used is statistically and applies only to a series of observations. Determination of the uncertainty value is done by performing repeated measurements five times on the same sample. This method refers to ISO GUM with type A evaluation. The uncertainty value obtained for the best measurement is 0.0034 mm with an expanded uncertainty of 0.0068 mm with a 95% confidence level.